(untitled) (Computer systems and information technologies, 2024)
This paper focuses on the design and evaluation of a FIPA standard compliant multi-agent platform. The relevance of the topic is due to the growing need for flexible, reliable, and efficient software solutions capable of solving complex intelligent problems in distributed environments. The study is dedicated to the problem of developing and evaluating an agent platform using the Kotlin programming language. The main goal of this work is to design and implement a modular, scalable, and adaptive agent platform. The existing frameworks for the development of multi-agent systems are reviewed, the key components of such systems are highlighted, and the advantages of using Kotlin in the context of a multi-agent architecture are discussed. The scientific contribution of the paper is the creation of a modern FIPA-compliant multi-agent platform that exploits the advantages of the Kotlin language. The performance and resource intensity of the developed system are analyzed, and the platform’s compliance with FIPA standards and its interoperability are evaluated. Two different metrics are used to ensure the quality of the system. One of the metrics is the percentage of covered code. This metric is measured using the kover library. We achieved 71.4% coverage of classes and 57.1% coverage of commands. Further coverage is complicated by the use of multi-threaded technologies. The second metric is the system’s score for comments from the sonarlint evaluation tool. During development, 16 comments were identified and fixed. This allows us to achieve a high level of code quality and ensure quality for the future. The study demonstrates the potential of integrating modern language capabilities with the multi-agent paradigm, opening new perspectives for the development of efficient and scalable solutions in the area of distributed intelligent systems.